2015
DOI: 10.1155/2015/391349
|View full text |Cite
|
Sign up to set email alerts
|

Audiomotor Integration in Minimally Conscious State: Proof of Concept!

Abstract: Patients suffering from chronic disorders of consciousness (DOC) are characterized by profound unawareness and an impairment of large-scale cortical and subcortical connectivity. In this study, we applied an electrophysiological approach aimed at identifying the residual audiomotor connectivity patterns that are thought to be linked to awareness. We measured some markers of audiomotor integration (AMI) in 20 patients affected by DOC, before and after the application of a repetitive transcranial magnetic stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 53 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…Interestingly, we found that the evaluation and modulation of SMI through NIBS was useful in UWS-fLIS differential diagnosis. We evaluated functional visuo-premotor-motor FC in UWS and MCS sample before and after the administration of an associative stimulation protocol composed of tDCS on the dorsolateral prefrontal cortex and parieto-occipital areas and trans-orbital alternating current stimulation [96,97]. Such an approach confirmed the clinically-based differential diagnosis with the exception of one patient in UWS who electrophysiologically behaved as those in MCS, and who regained consciousness some months later.…”
Section: Evoked Potentialsmentioning
confidence: 70%
See 2 more Smart Citations
“…Interestingly, we found that the evaluation and modulation of SMI through NIBS was useful in UWS-fLIS differential diagnosis. We evaluated functional visuo-premotor-motor FC in UWS and MCS sample before and after the administration of an associative stimulation protocol composed of tDCS on the dorsolateral prefrontal cortex and parieto-occipital areas and trans-orbital alternating current stimulation [96,97]. Such an approach confirmed the clinically-based differential diagnosis with the exception of one patient in UWS who electrophysiologically behaved as those in MCS, and who regained consciousness some months later.…”
Section: Evoked Potentialsmentioning
confidence: 70%
“…Such an approach confirmed the clinically-based differential diagnosis with the exception of one patient in UWS who electrophysiologically behaved as those in MCS, and who regained consciousness some months later. Therefore, passive audiomotor and visuomotor integration could be a promising tool to stimulate sensory networks FC, thus enabling physicians in the differential diagnosis among MCS, UWS, and fLIS [96,97]. Based on our studies, we can argue that patients UWS showing an improvement in cortical FC and motor output after a SMI-based NIBS approach should be considered as suffering from fLIS rather than UWS.…”
Section: Evoked Potentialsmentioning
confidence: 76%
See 1 more Smart Citation
“…A few preliminary TMS and transcranial direct current stimulation approaches targeting the left temporal region in chronic aphasic patients showed indeed significant improvement in language abilities (18,(64)(65)(66). An alternative promising approach to foster audiomotor integration ability, tested so far only in patients with disorder of consciousness due to severe brain injury, consisted in pairing auditory with transcranial magnetic stimuli on the primary motor area, using the stimulation paradigm known as paired associative stimulation, which induces associative LTP or LTD-like neuronal plasticity (67).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown in DOC samples that TMS and tDCS can unmask residual covert connectivity patterns in parallel to a behavioral responsiveness improvement [14,15]. Moreover, audiomotor and visuomotor stimulation could be promising tools to potentiate the functional connectivity within large-scale sensorymotor networks [16,17]. These new approaches exploring covert behaviors and functional connectivity may yield further insight into DOC pathophysiology and improve the differential diagnosis.…”
Section: Introductionmentioning
confidence: 99%